(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
A spectral Jacobi-collocation approximation is proposed for Volterra delay integro-differential equations with weakly singular kernels. In this paper, we consider the special case that the underlying solutions of equations are sufficiently smooth. We provide a rigorous error analysis for the proposed method, which shows that both the errors of approximate solutions and the errors of approximate derivatives decay exponentially in L^∞ norm and weighted L^2 norm. Finally, two numerical examples are presented to demonstrate our error analysis.